Toward understanding the role of G-protein signaling. (February 2021) - Kise, Ryoji; Ono, Yuki; Kawakami, Kouki; Inoue, Asuka
Abstract: G-protein–coupled receptors (GPCRs) regulate many facets of homeostasis by sensing extracellular signaling molecules. To exert a plethora of roles, GPCRs use divergent and intricate signaling networks. To better understand the role of GPCR signaling, it is an important goal to identify the contribution of every signal transducer and its effectors. Recent advances in methodologies have provided an unprecedented opportunity to characterize many aspects of GPCR signaling, including GPCR–G-protein coupling, selective activation of specific pathways, and the physiological roles of GPCR signaling. Taking advantage of their versatile properties, several methods have been used to generate extensive data sets comparing signaling through a large set of GPCRs. Here, we review recent progress in methodologies to dissect intricate GPCR signaling and discuss future directions of research on GPCR signaling.